Effect of night smoking, sleep disturbance, and their co-occurrence on smoking outcomes - Peters, Erica N.; Fucito, Lisa M.; Novosad, Claire; Toll, Benjamin A.; O'Malley, Stephanie S. (Psychology of Addictive Behaviors, 2011)
Recent evidence suggests that smoking during the night is an indicator of nicotine dependence and predicts smoking cessation failure. Night smokers are likely to experience disturbance to their sleep cycle when they wake to smoke, but we are not aware of the prevalence of night smokers' self-reported sleep disturbance. Because sleep disturbance also predicts smoking cessation failure, we examined how the pre-cessation risk factors of night smoking and sleep disturbance, and their co-occurrence, predict smoking cessation failure in a 6-week double-blind randomized controlled trial examining whether naltrexone augments the efficacy of the nicotine patch (O'Malley et al., 2006). Smokers (N = 385) completed the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and a single item of waking at night to smoke pre-cessation. Smoking status was determined at weeks 1, 6, 24, and 48 weeks after quitting. The two main findings were: (a) night smokers reported significantly greater sleep disturbance than nonnight smokers; and (b) smokers with co-occurring night smoking and sleep disturbance experienced significantly greater risk for smoking than smokers with neither risk factor. Results suggest that individuals who both wake during the night to smoke and report clinically-significant sleep disturbance represent a high-risk group of smokers. Future smoking cessation treatment might incorporate strategies related to managing these smokers' sleep habits and physiological dependence on nicotine in order to bolster their cessation outcomes.
Keywords: Adult; Double-Blind Method; Female; Humans; Male; Middle Aged; Night smoking; Outcome predictors; Pittsburgh Sleep Quality Index; Prevalence; Self Report; Sleep Disorders; Sleep disturbance; Smoking; Smoking Cessation; Smoking cessation; Tobacco Use Disorder; Treatment Outcome; adult; article; cigarette smoking; comorbidity; controlled study; dept.psy; double blind procedure; drug dose comparison; female; high risk patient; human; major clinical study; male; naltrexone; named inventories, questionnaires and rating scales; nicotine patch; night; placebo; prediction; randomized controlled trial; risk factor; sleep disorder; smoking cessation; smoking habit; tobacco dependence; treatment failure; wakefulness